Witch & Wizard: The Gift - Book 2 - Patterson, James 1947-; Rust, Ned (New York : Little, Brown, 2010)
After escaping imprisonment by the totalitarian regime known as the New Order, siblings Wisty and Whit Allgood, who possess magical powers, establish themselves as leaders of the Resistance, a hidden community of teenagers like themselves, hunted by the state and determined to defy its ban on the arts, magic, and all other forms of creativity.
Keywords: Brothers and sisters -- Juvenile fiction; Magic -- Juvenile fiction; Totalitarianism -- Juvenile fiction; Brothers and sisters -- Fiction; Magic -- Fiction; Totalitarianism -- Fiction